1999
DOI: 10.2115/fiber.55.8_349
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition Behavior of Polylactide Fabrics Treated with Flame Retardants.

Abstract: Abstract:The thermal decomposition behavior of polylactide fabrics treated with tetrabromobisphenol A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Textile is a major application for PLA and it is also required to achieve flame retardancy. The flame retardancy of PLA fabrics were investigated by Kubokawa et al [37][38][39] using conventional FR treatments measuring the limiting oxygen index (LOI measured according to the ASTM Standard Method D2863-97). Untreated PLA fabric was measured at 24 vol% and when treated with several bromine-containing flame retardants and a phosphoruscontaining flame retardant, triphenylphosphate (TPP), LOI increases slightly to 28 vol% with TPP and to 26 vol% with the bromine-containing FR (tetrabromobisphenol A or TBP-A which was revealed to be the most efficient).…”
Section: (B) Use Of Conventional Flame Retardantmentioning
confidence: 99%
“…Textile is a major application for PLA and it is also required to achieve flame retardancy. The flame retardancy of PLA fabrics were investigated by Kubokawa et al [37][38][39] using conventional FR treatments measuring the limiting oxygen index (LOI measured according to the ASTM Standard Method D2863-97). Untreated PLA fabric was measured at 24 vol% and when treated with several bromine-containing flame retardants and a phosphoruscontaining flame retardant, triphenylphosphate (TPP), LOI increases slightly to 28 vol% with TPP and to 26 vol% with the bromine-containing FR (tetrabromobisphenol A or TBP-A which was revealed to be the most efficient).…”
Section: (B) Use Of Conventional Flame Retardantmentioning
confidence: 99%
“…Bourbigot and Fontaine reported ammonium polyphosphate (APP) usage increased flame retardancy for polyamides and polyesters. In the studies of Kubokawa et al, results showed flame retardancy of PLA slightly improved with triphenyl phosphate (TPP). In another study, Lin et al showed aluminum hypophosphite loading enhanced flame retardancy of PLA/PC blends.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the flame retardancy of polymers, adding flame retardants is accounted as the most effective way . Conventional flame retardants including aluminum hydroxides (ATH), magnesium hydrate, antimony trioxide, phosphorus-containing compounds, halogenated compounds and silicon-containing compounds have been investigated in the fame retardancy of PLA. , Kubokawa et al reported that tetrabromobisphenol-A exhibited excellent flame retardancy for PLA . However, halogenated flame-retardants release caustic and toxic gases during combustion so that they are gradually replaced by other flame retardants.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Kubokawa et al reported that tetrabromobisphenol-A exhibited excellent flame retardancy for PLA. 12 However, halogenated flame-retardants release caustic and toxic gases during combustion so that they are gradually replaced by other flame retardants. According to Haruo et al, ATH improved the flame retardancy of PLA due to its physical effects, but relatively large amount of ATH decreased the mechanical properties of the flame-retarded materials.…”
Section: Introductionmentioning
confidence: 99%